Effect of biological treatment used before harvesting and storage methods on the quality, health and microbial characteristics of unripe hazelnut in the husk (Corylus avellana L.) - Markuszewski, Bogumił; Bieniek, Anna Adriana; Wachowska, Urszula; Bieniek, Arkadiusz; Krzymińska, Izabela (PeerJ, 2022)
Background The hazelnut (Corylus avellana) is still one of the most profitable nut crop species. In recent years, however, there has been growing interest in this species in the form of “fresh nuts” that are picked before falling out of the fruit cover. The aim of this study was to evaluate the effect of storage conditions for hazelnuts protected with biological preparations on selected morphological features of the fruits, their health status and the count of bacteria and fungi colonizing the fruits. Results The hazelnuts harvested from the trees protected with a preparation containing Pythium oligandrum and stored for 2 months under the controlled atmosphere conditions and in Xtend® bags (MAP) had the greatest weight and the highest percentage of the kernel. After 3 months of storage, the hazelnuts had reduced commercial value. Only a few hazelnuts displayed symptoms of infectious diseases caused by species of Botrytis and Monilia. The protection applied before the hazelnut harvesting contributed to a multiple increase in the bacterial and yeasts count on the husks and shells of the hazelnuts stored for 3 months. The bacterial count on the nuts stored under the controlled atmosphere (CA, 3%O2:3%CO2, a temperature of 0–1 °C, humidity of 85–95%) and under the controlled atmosphere conditions and in Xtend® bags (MAP) increased significantly. An analysis of the ITS region sequence revealed the presence of bacteria Arthrobacter luteolus and Pantoea agglomerans. A Koch test proved that both non-pathogenic bacteria and pathogenic fungi can cause the browning of the C. avellana leaf under conditions of high humidity. The application of a controlled atmosphere is recommended for a short-term storage of hazelnuts in the husk. Conclusion This research showed that 2 months’ storage of hazelnuts under controlled atmosphere conditions and Xtend® bags (MAP) prevented a reduction in the weight of hazelnuts in the husk, without the husk, and of the kernel and prevented the nut separation from the husk. In general, the application of biopreparations for the protection of the hazelnut had a positive effect on the kernel weight and size.
Keywords: Fresh hazelnut; Arthrobacter; Pantoea; Probiotics; Pythium oligandrum; Cladosporium